Penyelesaian Tindak Pidana Korupsi: Pandangan Hukum Internasional atas Kewenangan - Dyah Rosiana Puspitasari; Della Alvina (Universitas Sains dan Teknologi Komputer, 2023)
This research aims to provide a deeper understanding of the authority and mechanisms for resolving criminal acts of corruption across national borders from an international legal perspective, as well as to identify steps that can be taken to improve the handling of corruption cases globally. This research uses a descriptive-analytical approach, with secondary data obtained through literature studies, statutory policies related to Corruption including Law no. 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission, Law No. 7 of 2006 concerning Ratification of the United Nations Convention Against Corruption, 2003 (United Nations Convention Against Corruption. Results of this research shows that the authority to adjudicate in the context of resolving criminal acts of corruption is based on the principle of aut punire aut dedere. Perpetrators of crimes are punished by the country where the crime was committed or handed over to the state that has the authority and wishes to try them. In conclusion, although the authority to adjudicate lies in the country of origin of the perpetrator of the criminal act of corruption, Cooperation between countries is needed because the form of crime is transnational.